The Impact of 'Mlijo' Creative Dance Employing Diverse Teaching Methods on Motor Skills Development in 5 to 6-Year-Old Children - Lunna Wuryandari; Nur Afiyati; Aidha Putri Azmi (Global Education : International Journal of Educational Sciences and Languages, 2024)
This research investigates the influence of the creative dance "Mlijo" by applying various teaching methods on the development of gross motor skills in children aged 5 to 6 years. Through this approach, the researchers explored the impact of combining dance movements and learning strategies tailored to children's individual needs. This study aims to investigate the extent to which the creative dance "Mlijo" can improve gross motor skills in children of this age, as well as provide insight into the effectiveness of various teaching methods in the context of dance learning. Keywords: Creative Dance, Mlijo, Various Teaching Methods, Gross Motor Skills, Children Aged 5-6 Years